Analysis of Students' Mathematical Understanding on Arithmetic Sequences and Series in 12th Grade Senior High School - Qolbi, Gina; Dewi, Pusaki Aurani; Sholiha, Sintiya; Pangestu, Tio Alifka; Fu’adin, Ahmad (S&Co Publishing, 2022)
The purpose of this study was to analyze students' understanding to solve arithmetic sequences and series questions. The subjects of this study were students who are in the 12th grade at SMAN 2 Garut, and they were 77 persons has been selected randomly from two study groups with the same teacher. This research applied descriptive quantitative techniques. The research result shows that students' ability is still low in solving arithmetics questions. This research found that there are three categories of students based on their achievement scores, namely the low category with a percentage is 42%, the medium category with a percentage is 36%, and the high category with a percentage is 22%. Some factors causing students’ errors are ineffective learning, uncarefully solving questions, and students have been lack of understanding of the material.